LncRNAs and their regulatory networks in breast muscle tissue of Chinese Gushi chickens during late postnatal development - Li, Yuanfang (BMC Genomics, 2021)
BACKGROUND: Chicken skeletal muscle is an important economic product. The late stages of chicken development constitute the main period that affects meat production. LncRNAs play important roles in controlling the epigenetic process of growth and development. However, studies on the role of lncRNAs in the late stages of chicken breast muscle development are still lacking. In this study, to investigate the expression characteristics of lncRNAs during chicken muscle development, 12 cDNA libraries were constructed from Gushi chicken breast muscle samples from 6-, 14-, 22-, and 30-week-old chickens. RESULTS: A total of 1252 new lncRNAs and 1376 annotated lncRNAs were identified. Furthermore, 53, 61, 50, 153, 117, and 78 DE-lncRNAs were found in the W14 vs. W6, W22 vs. W14, W22 vs. W6, W30 vs. W6, W30 vs. W14, and W30 vs. W22 comparison groups, respectively. After GO enrichment analysis of the DE-lncRNAs, several muscle development-related GO terms were found in the W22 vs. W14 comparison group. Moreover, it was found that the MAPK signaling pathway was one of the most frequently enriched pathways in the different comparison groups. In addition, 12 common target DE-miRNAs of DE-lncRNAs were found in different comparison groups, some of which were muscle-specific miRNAs, such as gga-miR-206, gga-miR-1a-3p, and miR-133a-3p. Interestingly, the precursors of four newly identified miRNAs were found to be homologous to lncRNAs. Additionally, we found some ceRNA networks associated with muscle development-related GO terms. For example, the ceRNA networks contained the DYNLL2 gene with 12 lncRNAs that targeted 2 miRNAs. We also constructed PPI networks, such as IGF-I-EGF and FZD6-WNT11. CONCLUSIONS: This study revealed, for the first time, the dynamic changes in lncRNA expression in Gushi chicken breast muscle at different periods and revealed that the MAPK signaling pathway plays a vital role in muscle development. Furthermore, MEF2C and its target lncRNA may be involved in muscle regulation through the MAPK signaling pathway. This research provided valuable resources for elucidating posttranscriptional regulatory mechanisms to promote the development of chicken breast muscles after hatching. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-020-07356-6.